Concurrent Guillain-Barré syndrome, transverse myelitis and encephalitis post-Zika: A case report and review of the pathogenic role of multiple arboviral immunity (2018)
We review post-infectious and post-vaccination neurological syndromes involving peripheral and central nervous system (CNS) and report an illustrative case of simultaneous occurrence of Guillain-Barré syndrome (GBS), confirmed by nerve conduction velocities, plus MRI-demonstrated transverse myelitis (TM) and acute encephalitis [acute disseminated encephalomyelitis] (ADEM+GBS) affecting a 24-year-old woman from Cúcuta, Colombia, who developed acute Zika virus (ZIKV) infection confirmed by serum reverse transcriptase-polymerase chain reaction (RT-PCR) and convalescent ZIKV IgG antibodies. With intensive care treatment, respiratory support, steroids, and intravenous immunoglobulin (IVIg), patient survived with residual flaccid paraparesis. She had preexisting immunity against Chikungunya virus (CHIKV) and Dengue virus (DENV) acquired before the arrival of ZIKV in Colombia. From reports in the Caribbean, Central and South America we review 19 cases of ZIKV-associated TM, encephalitis and ADEM occurring after a mean latent period of 10.5 days (range 1–96) post-infection. Although GBS and ADEM are usually considered post-infectious and associated with development of antibodies against peripheral nerve and CNS epitopes, we postulate that our case of ADEM+GBS is para-infectious, induced by acute ZIKV neurotropism boosted by active immunity against other arboviruses. Animal models of ZIKV demonstrated strong viral neurotropism enhanced by passive immunity with antibodies against arboviruses such as West Nile virus, CHIKV, or DENV. These considerations are relevant to prevent potential ZIKV vaccine-induced reactions involving central and peripheral nervous system. © 2018 The Authors